Activities and outdoor play: Their benefits for physical, cognitive, and social learning and well-being - Alessandra Natalini; Fabio Orecchio (Pensa MultiMedia, 2022)
The outdoor environment, both natural and urban, is increasingly seen as a promising context to improve the population's development, learning and physical activity levels. Substantial evidence indicates that it contributes to healthier and more sustainable lifestyles. Physical activity in the outdoors gives children broad health and developmental benefits at all levels (Bento, & Dias, 2017), ensuring improved motor and cognitive development (Tandon et al., 2016) and general well-being (Carpenter & Harper, 2016), including obesity prevention (Hills, Andersen, & Byrne, 2011). However, nationally and internationally, children's varying degrees of physical activity are low, and time spent outdoors is decreasing (McGrath, Hopkins, & Hinckson, 2015) dramatically. Therefore, the identification of ways to promote play and, in general, outdoor activity has become an educational priority (Dozza, 2019; Farné, Bortolotti, & Terrusi, 2018) to ensure psycho-physical balance and significant learning. The use of outdoor spaces within school contexts could support an increase in outdoor time with evident benefits for physical, cognitive, affective-relational and social well-being (Becker et al., 2016) and a decrease in sedentary behavior (Nigg, 2021). The contribution focuses on making an examination of the evidence-based literature that highlights this relationship, focusing attention also on the importance of educationally incisive interventions, both in and out school, and a partnership coordination of local services.